Nordic Families, Children and Early Childhood Education - Garvis, Susanne; Harju-Luukkainen, Heidi; Sheridan, Sonja; Williams, Pia.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Largely as a result of social policies and cultural factors, the Nordic countries continually score high in lifestyle measures, quality of life and children's outcomes. This book brings together authors from the Nordic countries (Denmark, Finland, Iceland, Norway and Sweden) to share knowledge and understanding regarding families, children, primary education and children's leisure time activities. The empirical research and theoretical contributions provide important insights into the 'Nordic model' and explore the issues facing Nordic countries. The book reveals that while there are many similarities across the countries, differences also arise. The content of the book is more relevant now than ever, as countries look at better ways to support their populations. Nordic Families, Children and Early Childhood Education will be of interest to students and scholars across a range of disciplines, including Education, Sociology and Social Policy.
1. An Introduction to the Nordic countries: family, children and early childhood education -- 2. Children's Initiatives in the Finnish Early Childhood Education Context -- 3. Do children learn through play? How do we know? -- 4. Practicing Belonging in Kindergarten: Children's use of Places and Artefacts -- 5. Parental involvement in ECEC in Finland and in Sweden -- 6. Negotiating 'real families' in Swedish preschools -- 7. Instructional Strategies in Early Swedish Immersion in Finland -- 8. Children under the age of three in Norwegian childcare: Searching for Qualities -- 9. Systematic quality work in a Swedish context -- 10. Early Childhood Education (ECE) in the Nordic Countries: Universal Challenges to the Danish Model- Towards a Future ECE Paradigm.
Keywords: Sociology; Social groups; Early childhood education; Sociology of Family, Youth and Aging; Early Childhood Education